Dusky grouper massive die-off in a Mediterranean marine reserve - KERSTING, DIEGO K.; GARCÍA-QUINTANILLA, CELIA; QUINTANO, NAGORE; ESTENSORO, ITZIAR; ORTEGA-VILLAIZAN, MARÍA DEL MAR (Mediterranean Marine Science, 2024)
The dusky grouper Epinephelus marginatus (Lowe, 1834) is a key predator in shallow Mediterranean rocky habitats. Due to fishing pressure and slow population dynamics, dusky grouper populations are declining across their distribution range. Here we document a massive die-off of E. marginatus in the Columbretes Islands Marine Reserve (NW Mediterranean Sea) during the summer and early autumn of 2023. The mortality event was triggered by a Betanodavirus infection. Genetic characterization of isolates from the affected fish confirmed that they belong to the RGNNV genotype. Our findings indicate that such disease outbreaks can be particularly severe in areas with dense dusky grouper populations, potentially undermining the historical conservation effectiveness of marine protected areas. Although our results do not determine whether the infection originated from wild or farmed fish, it is essential to implement monitoring and early detection systems for Betanodavirus infections in both wild and farmed fish to prevent cross-infections.